Collaborative Dickens : authorship and Victorian Christmas periodicals - Klimaszewski, Melisa (Series in Victorian Studies., 2019)
"From 1850 to 1867, Charles Dickens produced special issues (called "numbers") of his journals Household Words and All the Year Round, which were released shortly before Christmas each year. In Collaborative Dickens, Melisa Klimaszewski undertakes the first comprehensive study of these Christmas numbers. She argues for a revised understanding of Dickens as an editor who, rather than ceaselessly bullying his contributors, sometimes accommodated contrary views and depended upon multivocal narratives for his own success. Klimaszewski uncovers connections among and between the stories in each Christmas collection. She thus reveals ongoing conversations between the works of Dickens and his collaborators--including Wilkie Collins, Elizabeth Gaskell, and understudied women writers such as Adelaide Anne Procter--on topics important to the Victorians, including race, empire, supernatural hauntings, disability, and criminality. By restoring links between stories from as many as nine different writers in a given year, Klimaszewski demonstrates that a respect for the Christmas numbers' plural authorship and intertextuality results in a new view of the complexities of collaboration in the Victorian periodical press and a new appreciation for some of the most popular texts Dickens published"--